A phase 2 study of ruxolitinib, an oral JAK1 and JAK2 inhibitor, in patients with advanced polycythemia vera who are refractory or intolerant to hydroxyurea. Issue 4 (30th October 2013) - Verstovsek, Srdan; Passamonti, Francesco; Rambaldi, Alessandro; Barosi, Giovanni; Rosen, Peter J.; Rumi, Elisa; Gattoni, Elisabetta; Pieri, Lisa; Guglielmelli, Paola; Elena, Chiara; He, Shui; Contel, Nancy; et al.
Abstract : BACKGROUND: Polycythemia vera (PV) is a myeloproliferative neoplasm associated with somatic gain‐of‐function mutations of Janus kinase‐2 ( JAK2 ). Therapeutic options are limited in patients with advanced disease. Ruxolitinib, an oral JAK1/JAK2 inhibitor, is active in preclinical models of PV. The long‐term efficacy and safety of ruxolitinib in patients with advanced PV who are refractory or intolerant to hydroxyurea were studied in a phase 2 trial. METHODS: Response was assessed using modified European LeukemiaNet criteria, which included a reduction in hematocrit to < 45% without phlebotomy, resolution of palpable splenomegaly, normalization of white blood cell and platelet counts, and reduction in PV‐associated symptoms. RESULTS: Thirty‐four patients received ruxolitinib for a median of 152 weeks (range, 31 weeks‐177 weeks) or 35.0 months (range, 7.1 months‐40.7 months). Hematocrit < 45% without phlebotomy was achieved in 97% of patients by week 24. Only 1 patient required a phlebotomy after week 4. Among patients with palpable splenomegaly at baseline, 44% and 63%, respectively, achieved nonpalpable spleen measurements at weeks 24 and 144. Clinically meaningful improvements in pruritus, night sweats, and bone pain were observed within 4 weeks of the initiation of therapy and maintained with continued treatment. Ruxolitinib treatment also reduced elevated levels of inflammatory cytokines and granulocyte activation. Thrombocytopenia and anemia were the most common adverse events. Thrombocytopenia of ≥ grade 3 or anemia of ≥ grade 3 (according to National Cancer Institute Common Terminology Criteria for Adverse Events, version 3.0) occurred in 3 patients each (9%) (1 patient had both) and were managed with dose modification. CONCLUSIONS: Ruxolitinib was generally well tolerated and provided rapid and durable clinical benefits in patients with advanced PV who were refractory or intolerant to hydroxyurea. Cancer 2014;120:513–20. © 2013 The Authors published by Wiley Periodicals, Inc. on behalf of American Cancer Society. Abstract : In the current study, patients with polycythemia vera who were refractory or intolerant to hydroxyurea achieved clinically meaningful and durable benefit from treatment with ruxolitinib with respect to reductions in hematocrit, platelet and white blood cell counts, splenomegaly, and symptoms. Given the limited therapeutic options for patients with advanced polycythemia vera, these results suggest that ruxolitinib has the potential to address an important unmet medical need in this patient population.